[PP.01.22] COMPARISON OF THE SPHYGMOCOR XCEL DEVICE WITH APPLANATION TONOMETRY FOR PULSE WAVE VELOCITY ASSESSMENT IN CHILDREN AND ADOLESCENTS. (September 2017) - Stabouli, S.; Printza, N.; Dotis, J.; Zervas, C.; Chrysaidou, K.; Maliachova, O.; Antza, C.; Kotsis, V.; Papachristou, F.
Abstract : Objective: Pulse wave velocity (PWV) is a well-recognized marker of arterial stiffness. Although the clinical value in children is not yet established its use is increasing in children and adolescents with cardiovascular risk factors. The gold-standard technique is tonometry, but this technique can be challenging, especially when used on children. The purpose of this study was to validate PWV assessment with novel oscillometric device (SphygmoCor XCEL) for use in children and adolescents. Design and method: Children and adolescents aged 5–20 years were recruited subsequently. Carotid-femoral PWV (PWVton) was measured by applanation tonometry with the "classic" Sphygmocor device and by SphygmoCor XCEL device (PWVosc). Regression analysis and Bland-Altman plots were used for comparison of the tonometer- to oscillometric-based method. ARTERY Society guidelines criteria were used to assess the performance of the oscillometric device. Results: Sixty-eight children and adolescents with mean age 11.5 ± 3.6 years, 32 (47.1%) male were included in the analysis. Mean pulse transit time was 81.48 ± 12.55 sec by the tonometric method, and 81.63 ± 12.24 sec by the oscillometric method (P = NS). Mean PWVton was 4.85 ± 0.81 m/sec and mean PWVosc 4.75 ± 0.81 m/sec. The mean difference between the two devices was 0.09 ± 0.47 m/sec (P = NS) and the accuracy of the oscillometric device was rated "excellent" according to the ARTERY Society guidelines (mean difference less than 0.5 m/s, SD of difference less than 0.8 m/s). Bland-Altman analysis showed good agreement with LoA ranging from -0.83 to 1.01. No proportional bias was detected by linear regression analysis with dependent variable the mean difference between devices and independent variable mean PWV of the two devices (B = 0.005, P = NS). In ANCOVA analysis, age and systolic blood pressure had no statistically significant effect on the mean difference between devices. Conclusions: The new oscillometric SphygmoCor XCEL device provides equivalent results for PWV values to those obtained by tonometry in children and adolescents. Thus, the SphygmoCor XCEL device is appropriate for assessing PWV in studies in the pediatric population.